2016
DOI: 10.1007/s12671-016-0501-4
|View full text |Cite
|
Sign up to set email alerts
|

Ontological Addiction: Classification, Etiology, and Treatment

Abstract: Despite the fact that there is increasing integration of Buddhist principles and practices into Western mental health and applied psychological disciplines, there appears to be limited understanding in Western psychology of the assumptions that underlie a Buddhist model of mental illness. The concept of ontological addiction was introduced and formulated in order to narrow some of the disconnect between Buddhist and Western models of mental illness, and to foster effective assimilation of Buddhist practices an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 35 publications
1
37
0
1
Order By: Relevance
“…The NAS also assesses the degree to which a person is “attached to themselves” because according to Buddhist theory, attachment to psychological or environmental phenomena arises due to a firm sense of selfhood (Shonin et al 2016). The NAS is constructed upon the Buddhist notion that the self does not inherently exist and that attachment to self and environment thus constitutes a maladaptive condition (see Shonin et al 2014 for a discussion of the differences between Buddhist and Western psychological conceptualisations of attachment).…”
Section: Methodsmentioning
confidence: 99%
“…The NAS also assesses the degree to which a person is “attached to themselves” because according to Buddhist theory, attachment to psychological or environmental phenomena arises due to a firm sense of selfhood (Shonin et al 2016). The NAS is constructed upon the Buddhist notion that the self does not inherently exist and that attachment to self and environment thus constitutes a maladaptive condition (see Shonin et al 2014 for a discussion of the differences between Buddhist and Western psychological conceptualisations of attachment).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the aforementioned empirical findings, support for the implementation of broadbased resilience-building approaches in adolescents derives from psychological models such as problem behaviour theory (Donovan et al 1991) and ontological addiction theory (Shonin et al 2016;Van Gordon et al 2018). These models assert that a given problematic behaviour or mental illness symptom is invariably an indicator of a more systemic maladaptive belief or unmet psychosocial need, which can manifest across multiple risk-taking behaviours or psychopathologies.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Indeed, some studies have shown that concepts such as emptiness can be challenging to identify with, particularly in less experienced meditators (Lomas, Cartwright, Edginton, & Ridge, 2015). However, an explanation for the improvements observed in the current study is posited by Ontological Addiction Theory (OAT), in which 'ontological addiction' is deemed to be the underlying cause of maladaptive cognitive and behavioural processes (Shonin et al, 2016;Van Gordon et al, 2018b). More specifically, ontological addiction is defined as "the unwillingness to relinquish an erroneous and deep-routed belief in an inherently existing 'self' or 'I' as well as the 'impaired functionality' that arises from such a belief" (Shonin et al, 2013, p.64).…”
Section: Discussionmentioning
confidence: 72%
“…(i) Non-Attachment Scale (NAS; Sahdra et al, 2010): The 30-item NAS is based on Buddhist philosophy and assesses the degree to which an individual becomes attached to their experiences on the psychological, social, and environmental plane. The NAS also assesses the degree to which a person is 'attached to themselves' because as previously discussed, according to Buddhist theory attachment to psychological or environmental phenomena arises due to a firm sense of selfhood (Shonin et al, 2016). The scale is constructed upon the Buddhist notion that the self is empty of inherent existence and that attachment to self and environment thus constitutes a maladaptive condition.…”
Section: Methodsmentioning
confidence: 99%